Kesan Banjir Akibat Pengaruh Air Pasang di Kawasan Mersing, Johor - Johari , Nornajibah; Seow, Ta Wee; Mohamed, Sulzakimin (Research in Management of Technology and Business, 2024)
Tidal flood is caused by the sea water rising to the level of the tide that floods the land. The problem of flooding in the study area is the implementation of unsystematic drainage systems, continuous rain and low-lying settlements. There are three objectives in the study which are to study the effects of tidal flooding among residents in the Mersing area, to identify the monitoring carried out by the Water and Drainage Department (JPS) and the parties involved in the change of tidal phenomenon causing flooding and to suggest effective alternatives for local residents when faced with the problem of flooding due to high tide in the study area. In the scope of the study, the researcher focused on some potential flood areas such as Kampung Lubok, Kampung Bahgia and Kampung Tenglu and Mukim Padang area. Next, the research methodology used is a mixed method, which is a combination of quantitative and qualitative methods to collect data in carrying out research to achieve the objectives of the study. The results of the study have been obtained showing that the most important effect of tidal flooding in the study area is the damage to agricultural areas because the land affected by flooding becomes unproductive and affects the decline of agricultural activities. Next, a systematic monitoring and management system is very important in overcoming the effects of flooding due to the phenomenon of high tides.For the third objective, an effective alternative is an alternative that is implemented correctly and is able to increase the resilience of local communities against floods and create a safer and more sustainable environment. There are other suggestions to overcome tidal flooding, which is to develop a topographic control system, build a system that handles garbage piles and the development of the drainage system. In conclusion, every community also needs to work with the authorities to do a joint initiative to deal with the problem of tidal flooding so that it can be reduced and overcome well so that there are no worse effects due to tidal flooding among the local population.